Theoretical Apparitions of Haiku : An Intermedial Interrogation of Modernity - Nelson, Tollof (Cinémas, 2000)
ABSTRACTAt the turn of the twentieth century, the translation and the reception of haiku poetry allowed for theoretical advances beyond the purview of the literary. The haiku-idiom reinvented itself as a practice of poetry as audio-visual technique : haiku as a line of flight, medium of another relationship to language and to images. A hybrid-model of the modernist arts (poetry photography, film), the haiku-idiom became a vehicle for theories articulating the experience of a new spatio-temporal economy of images. As a mode of writing in laconic fragments, gestures of everyday-life, and shadows of memory, the haiku-idiom mobilized for others a relationship of movement, opacity, and distance to language.